Effect of Hemodialysis on Some Biochemical Parameters in Diabetic Nephropathy Patients (Indian Journal of Forensic Medicine & Toxicology, 2020)
Diabetes mellitus is a worldwide epidemic and is associated with long-term damage and causes dysfunctionof several organs like kidney leading to diabetic nephropathy. This study was designed to evaluate somebiochemical aspects.This study was conducted on 95 patients which included (35) HD patients with diabetesand (35) HD patients without diabetes and (25) Type 2 diabetes mellitus patients, who attended at RamadiGeneral Hospital. For the purpose of comparison, (25) samples as control. Several tests were performed suchas FSB, urea, creatinine, glomerular filtration rate (GFR), albumin, sodium ion, calcium ion, Phosphorusion, potassium ion and magnesium ion were calculated. This study showed the level of urea and creatininewere a significant increase in HD patients with diabetes(128.29±22.59 and 7.1±1.76) mg/dl respectively,and HD patients without diabetes were (125.74±23.28 and 6.80±2.71) mg/dl respectively. The levels of Na+and Ca++ were decrease in HD patients with diabetes (137.6±4.8 mmol/L and 6.72±1.76mg/dl) respectively.The levels of P, K+ and Mg++ were a significant increase in HD patients without diabetes(6.26±0.84 mg/dl,5.52±0.61 mmol/L and 2.2±0.13mg/dl) respectively. The urea, creatinine and GFR are simple and usefulbiomarkers which can serve as predictor tests for assessing kidney functions in diabetic patients.